#SpoiledMilk: Blacktavists, Visibility, and the Exploitation of the Black Breast. Issue 1 (2nd January 2017) - Morrissey, Megan Elizabeth; Kimball, Karen Y.
ABSTRACT: On September 22, 2014, Medolac Laboratories, a company in Oregon that processes human milk, announced an initiative to purchase pumped breast milk from African-American mothers in Detroit, Michigan. Angry about Medolac's predatory initiative to target this population, a community of Black female breastfeeding activists, or Blacktavists, swiftly took to blogs, Twitter, and Facebook to express their concerns. We argue that Blacktavists—working on, against, and through the Black breastfeeding body—constructed a persuasive narrative about Medolac's campaign that made visible (a) the historical legacy of Black labor for White interests, (b) the economic value of that labor, and (c) whiteness as a racial category. Overall, our study explores the valuable, problematic, and complex characteristics of Blacktavists' advocacy. Future successful advocacy must continue to challenge normative mothering rhetorics to bring about impactful social change.